Evaluation of studies conducted on the "assessment-evaluation" dimension of 2004 primary school curriculum - Kazu, Hilal; Aslan, Serkan (Ankara University, 2013)
This research aimed to evaluate studies conducted on the "measurement and evaluation" dimension of 2004 primary curriculum. For that reason, descriptive scan model was used in the research. The meta-analysis and content analysis were employed to analyze research studies. The scope of the study is 49 declarations and 40 articles that were done for complementary measurement and evaluation approaches upon evaluation of new elementary curriculums between 2004 and 2011, and that could be reached by researchers. Evaluation has revealed these results: Studies are mostly between 2006 and 2010, qualitative and descriptive scan models are employed as research models, teachers are determined as target groups more, studies are conducted more in and west districts. Result and suggestions of conducted studies are included in this study, too. Lastly, evaluations based on studies are made and suggestions are developed considering result and suggestions of conducted studies.
2004 ilkö?retim programının "ölçme-de?erlendirme" boyutu ile i?lgili yapılan araştırmaların de?erlendirilmesi
Keywords: 2004 primary school curriculum; Constructivism; Measurement-evaluation dimension